VD_FINDINFO HC / 2011 / 604 vom 29. August 2011 - VD Tribunal cantonal (2011)
PRESCRIPTION, DROIT DU TRAVAIL, DROIT CANTONAL, DROIT PUBLIC | 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 46 al. 2 LJT, 16 al. 1 LPers-VD, 16 al. 3 LPers-VD, 16 LPers-VD, 104 CDPJ, 166 al. 2 CDPJ